1994
DOI: 10.1139/g94-148
|View full text |Cite
|
Sign up to set email alerts
|

Some evidence of incipient speciation in Drosophila kikkawai

Abstract: Altogether 11 geographic populations of Drosophila kikkawai were analysed from the viewpoint of karyotypic variation, inversion polymorphism and sexual isolation. The results revealed that of all the populations, the New Guinea population was the most genetically diverged, characterized by its distinct karyotype, possession of a fixed inversion, and its females exhibiting sexual isolation at the level of preferential mating. Based on these findings it was inferred that incipient speciation has proceeded in D. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…However, most of the studies showing this pattern used a ''no-choice'' mating design: females were paired with heterospecific males individually, and scored for whether they mated. Several studies have shown that choice mating experiments, where females may select between conspecific or heterospecific males, may yield different results from no-choice experiments (e.g., Gupta and Sundaran, 1994;Ryan and Rand, 1993;Wade et al, 1995), and some argue that choice experiments more accurately reflect the natural setting (e.g., Spieth and Ringo, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the studies showing this pattern used a ''no-choice'' mating design: females were paired with heterospecific males individually, and scored for whether they mated. Several studies have shown that choice mating experiments, where females may select between conspecific or heterospecific males, may yield different results from no-choice experiments (e.g., Gupta and Sundaran, 1994;Ryan and Rand, 1993;Wade et al, 1995), and some argue that choice experiments more accurately reflect the natural setting (e.g., Spieth and Ringo, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have already shown that choice and no-choice mating experiments may yield diverging results (e.g. Ryan & Rand 1993;Gupta & Sundaran 1994;Wade et al 1995;Coyne et al 2005). The respective advantages and disadvantages of choice versus no-choice mating experiments are still a matter of debate (see Casares et al 2005;Noor & Ortiz-Barrientos 2006).…”
Section: Discussion Male Ability To Use Pheromones To Discriminate Pomentioning
confidence: 99%
“…It is well known that there are cryptic species in many taxonomic groups, which is indistinguishable to each other at the morphological level, but can be identified at the genetic level [9][10][11][12][13]24]. Drosophila lacertosa populations have various degrees of karyotypic differentiation.…”
Section: Karyotype Differentiation In Drosophila Lacertosamentioning
confidence: 99%
“…Karyotype variation has been found not only among closely related species but also within one species [2][3][4][5][6][7][8]. Thus, cryptic and sibling species, or incipient speciation, has been frequently detected first at the cytological level for some insect species [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%